(untitled) (European Journal of Behavioral Sciences, 2023)
This research investigates the influence of Pope Francis’ encyclical Laudato Si on the attitudes and behaviors of Catholics regarding environmental stewardship in a post-COVID-19 context. The study employs a combination of quantitative and qualitative methods to comprehensively understand the impact of the encyclical and identify potential areas for future action and research in this critical field. The primary data collection involved a survey administered to 144 Catholic Youth Ministers in Mabalacat City, Pampanga. The survey included the Environmental Consciousness Scale and Christian Environmental Scale. Preliminary results indicate that Laudato Si has had a significant impact on Catholic perspectives and behaviors related to climate change and sustainability. The analysis of open-ended responses in the study provided valuable insights into the concerns and aspirations of the youth ministers. While personal aspects of life were the primary concerns for the youth, the youth ministers expressed deep concern about local pollution and the urban expansion on natural landscapes. They emphasized the importance of taking practical action to address these environmental issues and recognized the role of individual behaviors and societal structures in tackling these challenges. This research highlights the influential role of the Catholic Church in promoting environmental stewardship and the transformative power of religious teachings in elevating climate change concerns. The findings contribute to a better understanding of the influence of religious teachings on environmental attitudes and behaviors among Catholics. Furthermore, the insights generated in this study can inform policymakers, educators, and organizations seeking to promote environmental awareness and action among Catholic youth.